THERMOSENSITIVE MUCOADHESIVE PLURONIC-BASED IN-SITU VAGINAL GEL OF SERTACONAZOLE - Anita P. Patel, Anita P. Patel; Jayvadan K. Patel, Jayvadan K. Patel; Bharat Mishra, Bharat Mishra (International Journal of Indigenous Herbs and Drugs, 2019)
The purpose of this study is to develop thermosensitive mucoadhesive pluronics based in-situ gel of sertaconazole for treatment of vulvovaginal candidiasis, with the aim to prolong residence time in vagina, control drug release, and enhance efficacy as well as improvement in patient compliance. In-situ gel formulations of sertaconazole were formulated usingdifferent concentration of pluronic-127 alone and in combination with pluronic-68 as thermosensitive polymer and HPMC K4M also added as mucoadhesive polymer. The prepared formulations were evaluated for their gelation temperature, gelling capacity, rheological properties, mucoadhesive properties, microbiological studies and in vitro release studies. It was found that the viscosity and mucoadhesive force increased as theconcentration of pluronic-127 increasedand in vitro drug release decreased. In conclusion, HPMC K4M was able to improve the sustain release property of pluronics indicating that the combination of HPMC K4M and pluronics may find use in development of vaginal in-situgel drug delivery system with prolong local residence time and thus better clinical outcome.